ARTISTIK AND PEDAGOGICAL ACTIVITY OF REPRESENTATIVES OF LVIV CONDUCTING SCHOOL: MODERN ASPECT - Ярошенко, І. В. (SWorldJournal, 2022)
The study considers the аrtistic and pedagogical activity of representatives of Lviv conducting school: modern aspect . The author described the methodological principles of formation of the Lviv choral school and the specifics of pedagogical activity of